Clinical, Laboratory, and Placental Findings in Perinatal Listeriosis. (2nd September 2016) - Barikbin, Payman; Sallmon, Hannes; Hüseman, Dieter; Sarioglu, Nanette; Weichert, Alexander; von Weizsäcker, Katharina; Bührer, Christoph; Koehne, Petra
ABSTRACT: Clinical, laboratory, and placental manifestations of perinatal listeriosis are highly variable. Herein, we retrospectively analyzed all patients treated for neonatal listeriosis at the Charité University Medical Center in Berlin, Germany, 1999–2013. A total of 16 cases were identified. In 14 patients listeriosis was confirmed in neonatal specimens, while in two only the placenta tested positive. Elevated C-reactive protein and/or interleukin-6 levels were only inconsistently found, while a marked white blood cell left shift was present in all infants, if available. All but one infant manifested symptoms on the first day of life. Most patients required respiratory support, while none developed meningoencephalitis as evidenced by clinical or cerebrospinal fluid findings. Two patients died, all other patients survived without sequelae. In conclusion, perinatal listeriosis is still associated with significant morbidity and mortality. Clinical and laboratory findings are highly heterogeneous, but extreme leukocyte left shift seems to be a common feature.